2012
DOI: 10.1103/physrevb.86.075454
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-metal transition in semiconducting bilayer sheets of transition-metal dichalcogenides

Abstract: Using first-principles calculations we show that the band gap of bilayer sheets of semiconducting transition metal dichalcogenides (TMDs) can be reduced smoothly by applying vertical compressive pressure. These materials undergo a universal reversible semiconductor to metal (S-M) transition at a critical pressure. S-M transition is attributed to lifting the degeneracy of the bands at fermi level caused by inter-layer interactions via charge transfer from metal to chalcogens. The S-M transition can be reproduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
233
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 299 publications
(267 citation statements)
references
References 56 publications
33
233
1
Order By: Relevance
“…In agreement with prior theoretical studies 18,19,46 , our theoretically predicted band gap is found to depend inversely on pressure and that the critical pressure for the electronic phase transition is predicted to scale down for multilayered films from B16% normal compressive strain to B11% for bilayer MoS 2 ( Supplementary Fig. 8).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In agreement with prior theoretical studies 18,19,46 , our theoretically predicted band gap is found to depend inversely on pressure and that the critical pressure for the electronic phase transition is predicted to scale down for multilayered films from B16% normal compressive strain to B11% for bilayer MoS 2 ( Supplementary Fig. 8).…”
Section: Discussionsupporting
confidence: 76%
“…Hybrid Heyd-Scuseria-Ernzerhof 42 functional and DFT with many-body perturbation theory in the GW approximation 43 are among the few methods to correctly predict the band gap of TMDs; however, these methods are computationally very expensive. Nevertheless, our previous study for bilayer MoS 2 has shown that the overall nature of the variation in the E g and the band structure with pressure are independent of the functional used 18 and that the PBE functional gives reasonably accurate results, justifying the use of the PBE/GGA methods for this work. With the increase in pressure, the degeneracy in the bands of the unstrained structure is lifted due to the enhanced interlayer interaction.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the indirect-band gap of bilayer TMDCs can be driven to zero at an electric field of 2-3 Vnm −1 applied perpendicular to the layers, allowing for larger band gap tuneability than that in graphene [65]. Under strain, the band gap of mono-and bi-layer MoS 2 decreases and the material undergoes an insulator-to-metal transition [66][67][68][69]. Chemical stimuli can also modulate the band gap.…”
mentioning
confidence: 99%
“…3 Their band gaps, ranging approximately 1.0-2.5 eV, are normally at the K point in the Brillouin zone when direct. 3,4 Theoretical calculations predict intrinsic monolayer mobilities in the range of 25-410 cm 2 /Vs (electron) and 90-540 cm 2 /Vs (hole) for MX 2 , where M=Mo,W and X=S,Se. [5][6][7] Experimentally reported values are substantially smaller with the highest around 250 cm 2 /Vs (p-type).…”
mentioning
confidence: 99%